IMPLEMENTASI KEBIJAKAN IZIN TINGGAL WARGA NEGARA ASING DI KANTOR IMIGRASI KELAS I TPI KOTA PEKANBARU - Annisa Liona; Sujianto Sujianto (Cross-border, 2022)
A residence permit is a permit granted to a foreigner by a service official either manually or electronically to be in the territory of Indonesia. In practice, there is often misuse of residence permits. Misuse of residence permits is a legal event that often occurs in immigration crimes. Residence permits granted to foreigners to stay in the territory of the Indonesian state are often misused by the permit holders so that there are many cases of abuse of residence permits. The purpose of this study is to find out how to implement the Stay Permit Policy for Foreign Citizens at the Pekanbaru City Immigration Office and to find out what are the inhibiting factors for implementing the Stay Permit Policy for Foreign Citizens at the Pekanbaru City Immigration Office. This study uses a qualitative method with a descriptive approach, and in data collection using the methods of observation, interviews, and documentation. The results of the research obtained are that the implementation of the residence permit policy for foreign citizens at the Pekanbaru City immigration office has not run smoothly. There is still a lack of coordination between policy makers and implementers, resulting in weak supervision of foreign nationals in Pekanbaru City. And it can be seen from the results of the study, there are still foreign nationals who violate the provisions of the immigration administration such as exceeding the limit of their residence permit in Pekanbaru City. Then the inhibiting factor in the residence permit policy of Foreign Citizens in Pekanbaru City is the lack of supervision from the Pekanbaru City immigration office against foreigners who apply for residence permits, because there are still foreigners who violate the provisions of the immigration administration such as exceeding the limit of their stay permits (overstay). Even though the relevant agencies have supervised foreigners in accordance with existing procedures, only the foreigners themselves have made negligence, sometimes these foreigners ignore existing procedures at the immigration office so that immigration violations can be detrimental to themselves.